2019
DOI: 10.1088/1742-6596/1234/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Cu2SnS3 Thin Films Deposited by Fully Controlled System of Spray Pyrolysis

Abstract: A fully computerized system of spray pyrolysis was employed for fabricating copper tin sulphite ternary thin film onto glass substrates. During deposition process, the glass substrate was maintained at 310 ± 10 °C. After dissolving the raw chemicals, a mixture of their aqueous solutions was used for spraying process. The optimum solution mixture at the volumetric ratio [S/(Cu+Sn)=1] at 1.5 of pH. XRD investigation was approved a monoclinic phase of CTS. A number of different platform speed was tested in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The CN (g-C 3 N 4 ) synthesized through the pyrolysis of urea is a fluffy lightweight powder with a paleyellow color, while the CTS (Cu 3 SnS 4 ) synthesized through the coprecipitation process is a black precipitate with a slight For the synthesis of the CTS/CN composites, a known amount of CN was added to a precursor solution used for the synthesis of CTS (SnCl 4 and Cu(ac) 2 dissolved in distilled water) and sonicated for 30 min, followed by precipitation with the addition of the precipitating agent. A series of CTS/CN composites with varying contents of CTS (20,30,40,50, and 60% wt/wt). were prepared and labeled -20CTS/CN, 30CTS/ CN, 40CTS/CN, 50CTS/CN, and 60CTS/CN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CN (g-C 3 N 4 ) synthesized through the pyrolysis of urea is a fluffy lightweight powder with a paleyellow color, while the CTS (Cu 3 SnS 4 ) synthesized through the coprecipitation process is a black precipitate with a slight For the synthesis of the CTS/CN composites, a known amount of CN was added to a precursor solution used for the synthesis of CTS (SnCl 4 and Cu(ac) 2 dissolved in distilled water) and sonicated for 30 min, followed by precipitation with the addition of the precipitating agent. A series of CTS/CN composites with varying contents of CTS (20,30,40,50, and 60% wt/wt). were prepared and labeled -20CTS/CN, 30CTS/ CN, 40CTS/CN, 50CTS/CN, and 60CTS/CN.…”
Section: Resultsmentioning
confidence: 99%
“…44,48 For pristine CTS, the peaks around at 540 and 669 cm −1 could be attributed to the vibration of the Sn−S bond, 49,50 while the peak centered around 613 cm −1 is due to the vibrational mode of the Cu−S bond. 50,51 It could also be observed that the characteristic peaks of CN appeared in CTS/CN composites, but the characteristic peak due to the s-triazine ring vibration of CN nanosheets (at 809 cm −1 ) is shifted to 808 cm −1 for the composite, indicating the possibility of interactions between CN and CTS in the composite. 52 SEM and transmission electron microscopy (TEM) imaging techniques were used to elucidate the morphological and microstructural features of the CN, CTS, and 50CTS/CN composites.…”
Section: Structure and Morphologymentioning
confidence: 99%